PENGARUH NON PERFORMING LOAN ( NPL ) DAN LOAN TO DEPOSIT RATIO (LDR) TERHADAP NILAI PERUSAHAAN MELALUI PROFITABILITAS PADA PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA ( BEI ) PERIODE 2019-2021 - Sakdiyah, Wardatus; Wahyuni, Ika; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The era of globalization has made the economy very high in society; this development has changed financial services. People are used to digital trading in the midst of the Covid-19 pandemic. One of the companies providing financial services for economic growth today is the Bank. The purpose of this research is to analyze and test the effect of non-performing loans (NPL) and loan to deposit ratio (LDR) on company value through profitability in banking companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The populations in this study are banks listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 periods. The sampling technique used was purposive sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that Non-Performing Loans (Xâ‚) have a significant effect on Profitability (Y1), Loan To Deposit Ratio (X2) have a significant effect on Profitability (Y1), Non-Performing Loans (X1) have been proven does not have a significant effect on company value (Y2), Loan To Deposit Ratio has a significant effect on company value (Y2), Profitability (Y1) has a significant effect on company value (Y2), Non-Performing Loans (X1) has a significant positive effect on company value (Y2 ) through Profitability (Y), Non-Performing Loans (X1) has no significant negative effect on company value (Y2) through Profitability (Y1).